CTLA4 blockade with ipilimumab to treat relapse of malignancy after allogeneic hematopoietic cell transplantation - Bashey, Asad (American Society of Hematology, 2009)
Relapse of malignancy after allogeneic hematopoietic cell transplantation (allo-HCT) remains a therapeutic challenge. Blockade of the CTLA4 molecule can effectively augment antitumor immunity mediated by autologous effector T cells. We have assessed the safety and preliminary efficacy of a neutralizing, human anti-CTLA4 monoclonal antibody, ipilimumab, in stimulating the graft-versus-malignancy (GVM) effect after allo-HCT. Twenty-nine patients with malignancies that were recurrent or progressive after allo-HCT, received ipilimumab as a single infusion at dose cohorts between 0.1 and 3.0 mg/kg. Dose-limiting toxicity was not encountered, and ipilimumab did not induce graft-versus-host disease (GVHD) or graft rejection. Organ-specific immune adverse events (IAE) were seen in 4 patients (grade 3 arthritis, grade 2 hyperthyroidism, recurrent grade 4 pneumonitis). Three patients with lymphoid malignancy developed objective disease responses following ipilimumab: complete remission (CR) in 2 patients with Hodgkin disease and partial remission (PR) in a patient with refractory mantle cell lymphoma. At the 3.0 mg/kg dose, active serum concentrations of ipilimumab were maintained for more than 30 days after a single infusion. Ipilimumab, as administered in this clinical trial, does not induce or exacerbate clinical GVHD, but may cause organ-specific IAE and regression of malignancy. This study is registered at http://clinicaltrials.gov under NCI protocol ID P6082.